The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1007/s10915-022-01771-5
|View full text |Cite
|
Sign up to set email alerts
|

Data-Driven Modeling of Linear Dynamical Systems with Quadratic Output in the AAA Framework

Abstract: We extend the Adaptive Antoulas-Anderson () algorithm to develop a data-driven modeling framework for linear systems with quadratic output (). Such systems are characterized by two transfer functions: one corresponding to the linear part of the output and another one to the quadratic part. We first establish the joint barycentric representations and the interpolation theory for the two transfer functions of systems. This analysis leads to the proposed algorithm. We show that by interpolating the transfer fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 63 publications
(154 reference statements)
0
5
0
Order By: Relevance
“…In essence, if the damping matrix 𝐺 is defined via proportional damping with coefficients 𝛼 and 𝛽 as in Equation ( 7)), then Ref. [33] proposes choosing 𝑠 0 = √ 𝛼 𝛽 (14) as the interpolation point given an exact condenser distribution. In this case, as opposed to choosing multiple interpolation points and imposing the interpolation as in Equations (10,11) up to the first derivative, one chooses the single interpolation 𝑠 0 and matches 𝐻(𝑠) and its first 𝑟 − 1 derivatives at 𝑠 = 𝑠 0 .…”
Section: A Interpolation Point Selection Based On Exact Condenser Dis...mentioning
confidence: 99%
See 1 more Smart Citation
“…In essence, if the damping matrix 𝐺 is defined via proportional damping with coefficients 𝛼 and 𝛽 as in Equation ( 7)), then Ref. [33] proposes choosing 𝑠 0 = √ 𝛼 𝛽 (14) as the interpolation point given an exact condenser distribution. In this case, as opposed to choosing multiple interpolation points and imposing the interpolation as in Equations (10,11) up to the first derivative, one chooses the single interpolation 𝑠 0 and matches 𝐻(𝑠) and its first 𝑟 − 1 derivatives at 𝑠 = 𝑠 0 .…”
Section: A Interpolation Point Selection Based On Exact Condenser Dis...mentioning
confidence: 99%
“…Some of the projection-based techniques mentioned above (and employed in this paper) have been extended to the structured models we consider here; see, e.g., Ref. [14][15][16][17][18][19] and the references therein for some of the data-driven approaches to structured dynamics. However, this is not our focus in this paper and these considerations are left to future work.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, ERA is applicable to experiments and systems with full-state output. More recently, Gosea et al [52] extended this method for non-intrusive balancing transformation of continuous-time systems. Tu et al [53] showed that the linear operator obtained by ERA is related to the linear operator in dynamic mode decomposition (DMD) via a similarity transform.…”
Section: Introductionmentioning
confidence: 99%
“…The original formulation of the Loewner framework only considers the construction of unstructured systems (3), but it has been extended to find structured realizations in [44]. Recently, structured extensions of the barycentric form for second-order systems (4) have been proposed that allow the extension of further data-driven frequency domain methods to the structure-preserving setting [28,50].…”
Section: Introductionmentioning
confidence: 99%